A new middle Permian burnetiamorph (Therapsida: Biarmosuchia) from the South African Karoo filling a gap in the biarmosuchian record - Matlhaga, Fonda; Benoit, Julien; Rubidge, Bruce S (The Evolutionary Studies Institute, 2024)
Biarmosuchia, the most basal therapsid clade, is represented by relatively few specimens known from Permian deposits in Russia and southern Africa. In both the Guadalupian (middle Permian) and Lopingian (late Permian), biarmosuchians represent less than 1% of the fossil record at the specimen level. Here, we describe a new burnetiamorph biarmosuchian, Impumlophantsi boonstrai, based on a partial skull and associated postcrania from the upper Tapinocephalus Assemblage Zone. It is characterized by the presence of a low nasal crest with a unique morphology among burnetiamorphs. Inclusion of this taxon in an updated phylogenetic analysis of biarmosuchians indicates that this specimen is one of the most basal burnetiamorphs, representing the only record of this grade from the middle Permian.
Keywords: Synapsida; Burnetiamorpha; Permian; phylogeny; biostratigraphy